Degenerative Lumbar Spine Disease: Estimating Global Incidence and Worldwide Volume. Issue 8 (December 2018) - Ravindra, Vijay M.; Senglaub, Steven S.; Rattani, Abbas; Dewan, Michael C.; Härtl, Roger; Bisson, Erica; Park, Kee B.; Shrime, Mark G.
Study Design: Meta-analysis-based calculation. Objectives: Lumbar degenerative spine disease (DSD) is a common cause of disability, yet a reliable measure of its global burden does not exist. We sought to quantify the incidence of lumbar DSD to determine the overall worldwide burden of symptomatic lumbar DSD across World Health Organization regions and World Bank income groups. Methods: We used a meta-analysis to create a single proportion of cases of DSD in patients with low back pain (LBP). Using this information in conjunction with LBP incidence rates, we calculated the global incidence of individuals who have DSD and LBP (ie, their DSD has neurosurgical relevance) based on the Global Burden of Disease 2015 database. Results: We found that 266 million individuals (3.63%) worldwide have DSD and LBP each year; the highest and lowest estimated incidences were found in Europe (5.7%) and Africa (2.4%), respectively. Based on population sizes, low- and middle-income countries have 4 times as many cases as high-income countries. Thirty-nine million individuals (0.53%) worldwide were found to have spondylolisthesis, 403 million (5.5%) individuals worldwide with symptomatic disc degeneration, and 103 million (1.41%) individuals worldwide with spinal stenosis annually. Conclusions: A total of 266 million individuals (3.63%) worldwide were found to have DSD and LBP annually. Significantly, data quality is higher in high-income countries, making overall quantification in low- and middle-income countries less complete. A global effort to address degenerative conditions of the lumbar spine in regions with high demand is important to reduce disability.